Factors that matter in building and promoting psychological resilience of orphans and vulnerable children in Shurugwi rural district primary schools in Zimbabwe - Muguwe, Emely; Maposa, Laiza (Midlands State University, 2017)
The study sought to find out factors that matter in building psychological resilience in orphans and vulnerable children (OVCs) in rural primary schools in Zimbabwe. The four schools in the sample were randomly selected from one of the clusters of six schools (accessible population) within a total of sixty four primary schools in Shurugwi District. Twenty-four teachers out of eighty three teachers in the cluster were randomly selected, eight from each school. Four school heads were purposively selected. Teachers responded to a questionnaire while school heads participated in face-to -face interviews. Data were presented thematically in tables and verbatim. Results revealed that the family which is situated within the community plays the most significant role in building psychological resilience in OVCs, closely followed by the school through educational opportunities, then religion. Some of the strategies which could be used to build and promote resilience include having a supportive parent substitute, involving OVCs in religious activities, forming networks and counselling .Results also revealed that the government in partnership with Non-Governmental Organisations are the main support systems for OVCs.The implications of the study are that OVCs should by all means belong to a supportive family set up within the extended family. Schooling should be prioritised for them. The other implication is that government needs to strengthen its partnership with NGOs in providing psychosocial support for OVCs. The study recommends that the Ministry of Primary and Secondary Education should prioritise capacity building for teachers, increase support systems and availing all the necessary resources through partnerships with other stakeholders since these are considered to be key aspects in building and promoting psychological resilience in OVCs.